Parent’s Involvement and Challenges in Students Learning During Pandemic - SITI NOR AMIRA BAHARUDIN, TEO YEONG CHIN, ARVINDAN NAYAR, SITI NABILA BINTI SHEIKH SHAMSUL (Mathematical Statistician and Engineering Applications, 2023)
The Covid-19 pandemic has shifted the pattern of society’s existences to a new normative scenario, including the educational environment. Schools and educational institutions were forced to close until the Restricted Movement Order (RMO), or Movement Control Order (MCO) was promulgated. Many students and educators are unable to attend school on a regular basis owing to social contact constraints. As a result, parents must take on the responsibility of teaching and assisting their children’s online learning at home, which necessitates mastery of numerous topics, provision of internet connection and provision of suitable learning spaces and resources. This necessitates parents playing a critical part in ensuring students’ education continuity throughout the Covid-19 pandemic so that their children are not left behind in learning. The purpose of this research study is to find out how parents get involved in their children’s online learning. This study employed the survey and telephone interview data collection approach. Random sampling was utilized in this research study, with the sample criteria being parents with at least one school-aged child. The results indicated that every parent had different ways of getting involved in their children’s learning, each parent had to adapt with different types of challenges and each parent had different conceptions about digital tools. Future research is needed to identify the effects of online learning on the mental health of parents and children due to the Covid-19 pandemic, which might create more awareness towards society.